GENDER EQUALITY AND ECONOMIC DEVELOPMENT IN NIGERIA: THE ROLE OF CIVIL SOCIETY - KAZEEM ADEREMI ASIYANBI; AHMED YUSUF BABATUNDE; ADENIYI MICHAEL ADEWUSI (International Studies Journal)
Gender equality is widely acknowledged as a key driver of economic growth and social advancement. However, in Nigeria, severe gender inequities exist, limiting women's access to school, healthcare, economic opportunities, and political representation. These disparities jeopardize human rights and limit the country's capacity for long-term growth. Civil society groups (CSOs) have emerged as critical players in tackling these issues, pushing for gender parity, empowering women, and holding legislators responsible for enacting inclusive policies. This study investigates the role of civil society in promoting gender equality and economic development in Nigeria. It examines the techniques used by CSOs, assesses their impact on policy reforms and public attitudes, and analyzes the hurdles to accomplishing their goals. This study emphasized the literature rather than the major concerned respondents that have been the focus of previous researchers.  Using a systematic literature review, the research synthesizes existing studies on gender equality, economic development, and the contributions of CSOs to identifying gaps based on various authors' submissions on gender parity, trends, and best practices. The findings emphasize the necessity of collaboration among the government, civil society, and other stakeholders in building a more equal and prosperous Nigeria.